Tantangan Pemungutan Pajak Atas Transaksi E-Commerce Di Era Digital: Studi Implementasi Marketplace Sebagai Pemungut PPh Pasal 22 - silvia ananda putri; Puji Rahayu (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the challenges of tax collection on e‑commerce transactions in the digital era, focusing on the implementation of marketplaces as withholding agents for Article 22 Income Tax (PPh Pasal 22). The rapid growth of digital platforms has created new opportunities but also gaps in tax compliance, especially among micro, small, and medium enterprises (MSMEs). The research aims to analyze the effectiveness, legal certainty, and practical obstacles faced by marketplaces in fulfilling their role as PPh Pasal 22 collectors. A qualitative approach is used, combining legal analysis of tax regulations and case studies of selected marketplaces. Findings indicate that while the marketplace‑as‑withholding‑agent model improves tax visibility and simplifies administration, challenges remain in digital literacy, data integration, and coordination between platforms, sellers, and tax authorities. The study concludes with policy recommendations to strengthen the implementation framework and enhance voluntary compliance in the digital economy.